The Strategy, Impact, and Challenges Faced by Pos Malaysia Berhad during the COVID-19 Crisis - Daisy Mui Hung Kee; Siti Nurul Aisyah Nasser; Nur Syafiqah Mohd Sany; Tiara Iffah Azhar; Zhorifa Hazwani Roslan; Najwatul Adibah Amli (Journal of the Community Development in Asia (JCDA), 2021)
The current Covid 19 pandemic has caused many people to feel grateful for the work they still have. Millions of people have lost their jobs and livelihoods, economic problems and financial woes increase exponentially. The study aims to analyse the strategy, impact, and challenges faced by Pos Malaysia during the COVID-19 crisis. With operations scaled-down amidst the COVID-19 Pandemic, the company faced loss. The unprecedented COVID-19 pandemic has had significant impact on the companies, resulting the decrease of revenue for the first quarter in 2020. This study used a quantitative approach. An online survey was carried using Google Forms and the respondents were Pos Malaysia employees. By using a sample of 50 employees in Pos Malaysia, the result showed that Pos Malaysia business was affected due to the COVID-19 Pandemic and the subsequent stricter lockdown measures imposed in Malaysia.